2007
DOI: 10.1002/mc.20256
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of multiple anti‐apoptotic proteins in epidermis of IGF‐1 transgenic mice as revealed by 2‐dimensional gel electrophoresis/mass spectrometry analysis

Abstract: Overexpression of insulin-like growth factor-1 (IGF-1) has been associated with a number of human tumors, including breast, colon, lung, and prostate cancers. In previous studies, we found that mice overexpressing human IGF-1 in the basal layer of the epidermis (BK5.IGF-1 mice) developed skin tumors following treatment with the skin tumor initiator, 7,12-dimethylbenz[a]anthracene, indicating that IGF-1 can act as a skin tumor promoter. In the present study, we employed a proteomics approach of two-dimensional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Recently stromal expression of 14-3-3σ has been demonstrated in endometrial carcinomas and, similar to our results, the neoexpression by fibroblasts in areas of desmoplasia at the IF could be indicative of an active proinvasive environment within the extracellular matrix [40]. To provide more evidence of the role of 14-3-3σ in cancer development, recently it has been shown that 14-3-3σ provides chemoresistance properties to SCC and this fact, along with the anti-apoptotic properties of 14-3-3σ in tumoral cells, highlights the potential of this protein as a very promising biomarker and therapeutic target for penile SCC [18,[41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…Recently stromal expression of 14-3-3σ has been demonstrated in endometrial carcinomas and, similar to our results, the neoexpression by fibroblasts in areas of desmoplasia at the IF could be indicative of an active proinvasive environment within the extracellular matrix [40]. To provide more evidence of the role of 14-3-3σ in cancer development, recently it has been shown that 14-3-3σ provides chemoresistance properties to SCC and this fact, along with the anti-apoptotic properties of 14-3-3σ in tumoral cells, highlights the potential of this protein as a very promising biomarker and therapeutic target for penile SCC [18,[41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…Silencing of SNCG inhibits IGF-I-induced expression of GRP78, an IGF-Iresponsive molecular chaperone (46). Given that GRP78 is a multifunctional protein involved in diverse cellular processes, including the folding and processing of newly synthesized proteins, regulation of calcium homeostasis, modulation of the unfolded protein response, and drug resistance (47), SNCG may indirectly regulate these cellular processes through IGF-IR and GRP78.…”
Section: Discussionmentioning
confidence: 99%
“…IGF-1 transgenic mice developed skin tumors by DMBA, and both the mitogenic and anti-apoptotic pathways were upregulated (21). In the epidermis of IGF-1 transgenic mice, galectin-7 expression was reported to be 3-fold higher, compared to non-transgenic mice (22). Moreover, recently it was reported that galectin-7 is the most up-regulated molecule when benign lymphoma cells progress to the metastatic variant (17).…”
Section: Discussionmentioning
confidence: 99%